TREATMENT AND PREVENTION OF POST-CHEMOTHERAPY THROAT DRYING IN ONCOLOGY PATIENTS WITH NATURAL DRUG – ISLA MINT - TINATIN GOGNADZE; SHORENA TSIKLAURI; GHANATE RAHUL KUMAR; RAGINI; NIKHIL KUMAR (EXPERIMENTAL & CLINICAL MEDICINE GEORGIA, 2021)
Isla Mint is a natural drug, which has been used to treat the inflammation and dryness of oral mucosa, is extracted from the plant Iceland moss (Scientific name:Cetraria islandica). It contains substances that are characterized by its protective mucous membrane effects and its anti-irritant effect. The dose and therapeutic effectiveness have been analyzed in this clinical study. Isla Mint ბუნებრივი პრეპარატია, რომელიც გამოიყენება პირის ღრუს ლორწოვანი გარსის ანთების და სიმშრალის სამკურნალოდ. იგი მიიღება მცენარე ისლანდიის ხავსიდან (სამეცნიერო სახელი: Cetraria islandica) და შეიცავს ნივთიერებებს, რომლებიც ხასიათდება ლორწოვანი გარსის დამცავი ეფექტით და ანთების საწინააღმდეგო მოქმედებით. დოზა და თერაპიული ეფექტურობა გაანალიზებულია ამ კლინიკურ კვლევაში.